Evolução clínica e laboratorial de crianças nascidas de mães HIV positivas, com ênfase no uso do protocolo ACTG 076 - Silva, Margareth Jamil Maluf e (2007)
Vertical transmission constitutes the main via for children infection by the HIV-1 virus (Human Immune Deficiency Virus), which is responsible for about 80% to 90% of AIDS cases (Acquired Immune Deficiency Syndrome) in children from Brazil and worldwide. Vertical transmission became the main prophylaxis target with the ACTG 076 Protocol (AIDS Clinical Trial Group), which implicates the use of Zidovudine during the pregnancy, delivery and newborn. This research aimed at studying the laboratory and clinical evolution of children born from mothers acknowledged as HIV + infected, at the HIV/AIDS pediatric Specialized Assistance Service of the Hospital Materno-Infantil da Universidade Federal do Maranhão, highlighting the report on the use of the ACTG 076 Protocol, from January 1998 to June 2006. Information were obtained from the medical chants, through the protocol form with data related to the identification, laboratory and clinical evolution of 181 selected children via the inclusion criterion (born from mothers known to be HIV /AIDS infected that had their case diagnosis defined during the follow-up until June 30, 2006). In 36.5% of the mothers the diagnosis was done after delivery, the ACTG 076 Protocol was not used in 54.7% of the cases during pregnancy or delivery, and 49.2% did not use the protocol during the newborn period. Vaginal delivery occurred in 40.3% of the mothers and breastfeeding was practiced by 38.1% of the babies. The use of the full ACTG 076 Protocol (in all of the prescribed stages) was observed in 15.5%; partial usage of the protocol was conducted just with the newborns in 5.5%; partial usage just during pregnancy and/or delivery occurred in 1.1%, and the incomplete use was observed in 23.7%; 45% did not use the protocol in any of the prophylaxis stages. Out of the babies who had AIDS (41.9%), one could observe that 12.1% of the cases were classified in the clinical class A; 13. 7% in the class B and 10% in the class C, and they evolved with a variety of signs and symptoms, whose the most frequent were: hepatomegaly, splenomegaly, adenomegaly, neuropsychomotor development delay, and infection of the upper respiratory tract. The anti-HIV ELISA, the viral load determination, and the T CD4+ Lymphocytes counting were not routinely performed in many cases, at the first medical consultation. Infection diagnosis was mainly done by ELISA and, then, by confirmatory lab tests, without determining the viral load. The lymphocytes counting was restricted to classify the AIDS cases and to the follow-up treatment. Thus, in our study, several relevant factors were observed that demonstrate great improvements in the reduction of HIV vertical transmission, but also advise the importance of the continuous maintenance of intervening actions, principally with the organizational improvement of the reference services for clinical attendance and the conduction of laboratory exams.